Inattention Blindness to Motion in Middle Temporal Area - Harrison, Ian T. (Society for Neuroscience, 2013)
Subjects naturally form and use expectations to solve familiar tasks, but the accuracy of these expectations and the neuronal mechanisms by which these expectations enhance behavior are unclear. We trained animals (Macaca mulatta) in a challenging perceptual task in which the likelihood of a very brief pulse of motion was consistently modulated over time and space. Pulse likelihood had dramatic effects on behavior: unexpected pulses were nearly invisible to the animals. To examine the neuronal basis of such inattention blindness, we recorded from single neurons in the middle temporal (MT) area, an area related to motion perception. Fluctuations in how reliably MT neurons both signaled stimulus events and predicted behavioral choices were highly correlated with changes in performance over the course of individual trials. A simple neuronal pooling model reveals that the dramatic behavioral effects of attention in this task can be completely explained by changes in the reliability of a small number of MT neurons.